Foreign aid and developing countries' creditworthiness - Philipp Harms; Michael Rauber (Swiss National Bank, Study Center Gerzensee, 2004)
We explore whether foreign aid affects developing countries' creditworthiness, as proxied by the Institutional Investor's measure of country credit risk. Based on a simple model of international borrowing and lending, we develop the hypothesis that current aid reduces the likelihood of future default. We then test this hypothesis, using a data set that covers a large number of developing countries in the 1980s and 1990s. While the size of the effect differs across types of aid and country groups, our empirical findings support the notion that aid improves countries' standing vis-a-vis international capital markets.
Keywords: F34; F35; O16; O19; 330; Aid; International Investment; Country Risk; Dynamic Panel Estimation; Entwicklungshilfe; Länderrisiko; Entwicklungsländer; Schätzung